From barcodes to genomes: a new era of molecular exploration in bryophyte research - Dhyani, Anshul; Kasana, Shruti; Uniyal, Prem Lal (Frontiers in Plant Science, 2025)
Bryophytes represent a diverse and species-rich group of plants, characterized by a remarkable array of morphological variations. Due to their significant ecological and economic roles worldwide, accurate identification of bryophyte taxa is crucial. However, the variability in morphological traits often complicates their proper identification and subsequent commercial utilization. DNA barcoding has emerged as a valuable tool for the precise identification of bryophyte taxa, facilitating comparisons at both interspecific and intraspecific levels. Recent research involving plastomes, mitogenomes, and transcriptomes of various bryophyte species has provided insights into molecular changes and gene expression in response to environmental stressors. Advances in molecular phylogenetics have shed light on the origin and evolutionary history of bryophytes, thereby clarifying their phylogenetic relationships. Despite these advancements, a comprehensive understanding of the systematic relationships within bryophytes is still lacking. This review synthesizes current molecular studies that have been instrumental in unraveling the complexity of bryophyte taxonomy and systematics. By highlighting key findings from recent genetic and genomic research, we underscore the importance of integrating molecular data with traditional morphological approaches. Such integration is essential for refining the classification systems of bryophytes and for understanding their adaptive strategies in various ecological niches. Future research should focus on expanding the molecular datasets across underrepresented bryophyte lineages and exploring the functional significance of genetic variations under different environmental conditions. This will not only enhance our knowledge of bryophyte evolution, but also inform conservation strategies and potential applications in biotechnology.